Selected Works for Piano (Piano Solo and Piano, Four Hands) - Nietzsche, Friedrich Wilhelm 1844-1900; Hopkins, Nicholas (New York : Carl Fischer, 2017)
The philosopher Nietzsche was influenced heavily by music, and wrote many pieces in his younger days. This volume contains several of his works for piano solo and piano duet. With an introduction, notes on the pieces, and critical commentary. Facsimile plates.
Allegro (for piano solo) -- Albumblatt = Album page (for piano solo) -- Da geht ein Bach = There goes a brook (versions for solo piano) -- Da geht ein Bach = There goes a brook (version for voice and piano) -- Édes titok = Sweet secret (for piano solo) -- Das Fragment an sich = The fragment in itself (for piano solo) -- Einleitung = Introduction (for piano solo) -- Ermanarich : Symphonische Dichtung = Symphonic poem (for piano solo) -- Hymnus auf die Freundschaft = Hymn to friendship (version for piano solo) -- Heldenklage = Hero's lament (for piano solo) -- So lach doch mal! = Come on now, laugh! (for piano solo) -- Im Mondschein auf der Puszta = In the moonlight on the plains (for piano solo) -- Ungarischer Marsch = Hungarian March (for piano solo) -- Unserer Altvordern eingedenk! : Zwei polnische Tänze = To our predecessors : two Polish dances (for piano solo) -- Vivace (for piano solo) -- Manfred--Meditation (for piano, four hands) -- Monodie à deux : Lob der Barmherzigkeit = Monody for two : in praise of compassion (for piano, four hands) -- Nachklang einer Sylvesternacht : mit Prozessionslied, Bauerntanz und Mitternachtglocke = Echo of a New Year's Eve with processional song, peasants' dance and midnight bell (for piano, four hands) -- Phantasie (for piano, four hands) -- Untitled (for piano, four hands).
Includes bibliographical references.
Keywords: 19th Century (1801-1900); Piano; Keyboard music